Rehabilitation of Patients with Stroke - A Review - Shakoor, MA; Rahman, MS; Jaigirdar, MQH; Nahar, S; Moyeenuzzaman, M (Journal of Bangladesh College of Physicians and Surgeons, 2007)
(J Bangladesh Coll Phys Surg 2006; 24 : 114-118)